Measles Virus Imported by International Traveler in Jiangsu Province of China, in 2018 and 2019 - Ying Hu; Xiuying Deng; Peishan Lu; Hongxiong Guo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Measles remains a public health concern in many regions, and the imported measles cases continue to challenge the measles elimination program for most of the countries where measles was verified to be eliminated or approaching elimination. The imported measles cases have been reported since October, 2017, in Jiangsu province, China. In this study, we reported the first imported B3 genotype measles virus from Egypt and the second imported D8 genotype measles virus from Philippines through international traveling. No secondary measles cases were found after these imported cases. Our findings highlighted the importance of measles vaccination targeting international travelers in China.